Eventos de sedimentação e paleoclimáticos na transição Carbonífero-Permiano da bacia do Parnaíba, região de Teresina (PI) - ARAÚJO, Everson Moura de (2019)
The Piauí and Pedra de Fogo formations correspond to the Balsas Group, and record events of sedimentation in the transition from Carboniferous to Permian, in the Parnaíba Basin, Palmeiras region, Piauí. This break was marked by paleogeographic and paleoclimatic changes associated with the continental collisions that resulted to the development of the Pangea supercontinent, and implementation of a desert lacustrine system. By the facies analysis of the studied succession was possible the individualization of 11 sedimentary facies grouped in 4 sedimentary facies associations (FA): FA1 and FA2, related to deposits of Piauí Formation; and FA3 and FA4, relevant to deposits of the Pedra de Fogo Formation. The associations FA1- Field of dunes and FA2- Sand sheet are formed predominantly by sandy facies as fine to medium sandstones with tangential cross bedding of small to medium size, climbing ripple lamination translatent and plane-parallel, and sandstones with adhesion structures and massive mudstones. The facies association FA3 - continental Sabkha is characterized by the occurrence of fine sandstones with silicified levels, sandstones and laminated mudstones. The association FA4 – shallow Lacustrine consists of very fine to fine sandstones with climbing ripple lamination, interspersed with siltstones with wavy lamination to plane-parallel. These deposits of rocky stacking have 300 m thick and 26 m long are made by facies that form a set of tabular layers.